The impact of problematic substance use on partners' interpersonal relationships: qualitative analysis of counselling transcripts from a national online service. (3rd September 2019) - Wilson, Samara R.; Lubman, Dan I.; Rodda, Simone; Manning, Victoria; Yap, Marie B. H.
Abstract: Background: Problem alcohol or other drug (AOD) use can have severe impacts on partners interpersonally, including both their intimate relationship, as well as their interactions with friends and family. Previous research has predominantly focussed on spouses of problem drinkers, and recruited individuals who have experienced significant harm requiring medical or legal services. This paper sought to explore the breadth of interpersonal impacts on a broader range of partners, to better inform service provision. Method: One hundred synchronous online counselling transcripts of partners (85% female, aged 15 to over 65 years) of individuals with problem AOD use were sampled from a 24-hour national online AOD counselling service. A thematic analysis was conducted, exploring the interpersonal impact on partners. Findings: Interpersonal impacts included intimate relationship issues (discovery leads to communication difficulties; decisions to stay or leave), challenges in parenting (safety and well-being concerns; exposure to problem AOD use impacts; difficulty managing parenting responsibilities; pregnancy-related considerations), and impacts on and from their social network (benefits and challenges in seeking social support; extended family and social group stressors/support). Conclusions: Interpersonal impacts are multi-faceted, and partners should have access to targeted referrals for relationship assistance, peer support (online or face-to-face), domestic violence and welfare services.